A medicalização da queixa escolar: Poder e saber médico na produção de sujeitos em uma escola municipal de Santo Antônio do Sudoeste-Pr - Ortega, Fabiola Regina. (2019)
The present study analyzed the theme of medicalization of school complaint and the relationship of power and know doctor in the production of normalized subjects in Professor Guilherme Blick Municipal School. It was problematized, in the development of research, about hegemonic discursive practices in the subjectivation process of the learning subjects in this educational institution. The general objective consisted of analyzing the power relations and knowledge produced in the school, regarding the medicalization of children who are considered deviant from the standard standardization of ducts, and the effects of these discursive and non-discursive practices on the subjectivation processes of students. Through the reading of poststructuralist authors, approach used for the theoretical basis, notably from Michel Foucault (1977), shows that from the 18th century the questions of existence, behavior, conduct and the body were incorporated into a wide network of medicalization, how much more it works, the less it escapes medical knowledge. Medicine that acts in the control of the bodies / behaviors, standing between power and legal knowledge - that forbids action - and the power and knowledge of the humanities - that seeks to normalize behaviors. In this work the medicalization of education is understood as being the whole process that reduces the school complaint to a problem solely of organic and / or biological order. For the investigation of the theme used the qualitative bias research, based on the case study method, made through participant observation, documental analysis and semi-structured interviews applied to students, parents and teachers. For the analysis, Foucault's genealogy was adopted because it allows understanding about the relationship between power and medical knowledge, which affects the pedagogical space and produces ways of being and being in the school environment, contributing to the construction of subjectivities present in this context. As a result of this investigation, it was observed, among other issues, that medical knowledge has a power that stands out in this institution. However, religious, psychological, legal and disciplinary power and knowledge appeared in the discourses and movements made by school practices, showing that the institutional reality is dynamic and can make changes. It is considered that this research does not exhaust the possibilities of investigation on the medicalization of the school complaint. However, it contributes significantly to our understanding about medical knowledge and power, which makes up a discipline, control and normalization of the behavior of students, notably in the researched educational institution.